The relationship between physical activity towards anxiety and stress levels among college students - Desi Mevlana Saputri; I Gusti Ayu Artini; Gede Parta Kinandana; M. Widnyana (Physical Therapy Journal of Indonesia, 2023)
Background: A healthy body condition is a vital thing everyone needs, which can be achieved by doing enough physical activity. As final-year students who will end their studies in college, students will make a final project, commonly called a thesis. While finishing their thesis, students are at risk of experiencing anxiety and stress disorders. Anxiety and stress, when they occur continuously, irrationally, uncontrollably, and with increased intensity, anxiety, and stress can interfere with daily activities and lead to further mental disorders. This study aims to determine the relationship between physical activity and anxiety and stress levels in final-year students. Methods: This cross-sectional analytic study was conducted from November 2022 to February 2023. The sample was collected using a stratified random sampling technique, with 98 final-year students preparing their thesis. Physical activity was measured using the global physical activity questionnaire (GPAQ), anxiety level used the Hamilton anxiety rating scale (HARS), and stress level used the perceived stress scale (PSS). Results: Based on Spearman's rho analysis test, the results show that there was a relation between physical activity and anxiety level (p=0.000) with moderate correlation strength (r = -0.459), and there was a relation between physical activity and stress level (p=0.001) with low correlation strength (r=-0.331). Conclusion: There was a relationship between physical activity and anxiety and stress levels in final-year students of the Medical Faculty, Universitas Udayana, Bali, Indonesia. Background: A healthy body condition is a vital thing everyone needs, which can be achieved by doing enough physical activity. As final-year students who will end their studies in college, students will make a final project, commonly called a thesis. While finishing their thesis, students are at risk of experiencing anxiety and stress disorders. Anxiety and stress, when they occur continuously, irrationally, uncontrollably, and with increased intensity, anxiety, and stress can interfere with daily activities and lead to further mental disorders. This study aims to determine the relationship between physical activity and anxiety and stress levels in final-year students. Methods: This cross-sectional analytic study was conducted from November 2022 to February 2023. The sample was collected using a stratified random sampling technique, with 98 final-year students preparing their thesis. Physical activity was measured using the global physical activity questionnaire (GPAQ), anxiety level used the Hamilton anxiety rating scale (HARS), and stress level used the perceived stress scale (PSS). Results: Based on Spearman's rho analysis test, the results show that there was a relation between physical activity and anxiety level (p=0.000) with moderate correlation strength (r = -0.459), and there was a relation between physical activity and stress level (p=0.001) with low correlation strength (r=-0.331). Conclusion: There was a relationship between physical activity and anxiety and stress levels in final-year students of the Medical Faculty, Universitas Udayana, Bali, Indonesia.